Identifying the impact of meritocracy on human resource productivity from the perspective of police academy lecturers - Fetrat, Mohammad Ali; Mutahar, Sema (International Journal of Innovative Research and Scientific Studies, 2020)
The present study was conducted to "identify the impact of meritocracy on human resource productivity from the perspective of police academies". This research is a descriptive-survey research in terms of purpose and methodology. The statistical population of this study is all lecturers of Kabul Police Academy. Morgan table was used to determine the sample size, which according to the population of the sample required 121 people. The instrument or the device of this study is a complex questionnaire. The reliability of this questionnaire was confirmed by Cronbach’s alpha coefficient of 0.85. SPSS software was used to analyze the data using regression analysis. The results of this study show that meritocracy has a significant effect on human resource productivity, it also the effect of meritocracy components (knowledge, consciousness, abilities, skills, attitudes, education, training, and retention) on productivity. Human resources are influential and the hypotheses are confirmed.